O Level islamiyat preparation & examination (second edition) - Rehman, Habib ur (Paramount publioshing enterprises Lahore, 2007)
"O Level Islamiyat Preparation & Examination" by Habib ur Rehman is a comprehensive guide designed to assist students in effectively preparing for their O Level Islamiyat exams, offering key insights, practice questions, and structured content based on the syllabus.